2021
DOI: 10.1177/08874034211021894
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Procedural Justice Policy Adherence During Use of Force Events: The Body-Worn Camera as a Performance Monitoring Tool

Abstract: This study capitalizes on a successful researcher–practitioner partnership to conduct a systematic social observation (SSO) of police body-worn camera (BWC) footage in Newark, NJ. To demonstrate the utility of BWCs as performance monitoring tools, we measure officer adherence to procedural justice standards throughout use of force events as mandated in the Newark Police Division’s updated policies pursuant to an ongoing federal consent decree. Overall, a slim majority of use of force events are procedurally ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…They found that a slim majority of use of force events are procedurally just, but certain standards (e.g., addressing suspect concerns and using respectful language) were observed in a minority of cases. Further, most officers in Sytsma et als’ (2021) sample adhere to the agency policy of using escalating verbal commands before resorting to physical force.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…They found that a slim majority of use of force events are procedurally just, but certain standards (e.g., addressing suspect concerns and using respectful language) were observed in a minority of cases. Further, most officers in Sytsma et als’ (2021) sample adhere to the agency policy of using escalating verbal commands before resorting to physical force.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Accordingly, validated coding systems for BWC footage in the literature that assess officer performance in actual police-community interactions are limited. Notable exceptions include Willits and Makin (2018), who coded BWC footage of use-of-force incidents to assess the influence of various situational characteristics on the type, duration, and severity of the use of force; Holliday and Makin (2021), who coded BWC footage of police-community member encounters to assess the baseline frequency of uncivil behavior among officers and community members; and Sytsma et al (2021), who coded BWC footage of useof-force incidents using SSO to assess officer adherence to procedural justice standards. Despite these advances, a validated tool for measuring police-community interactions and officer performance more generally from BWC footage has yet to be put forward for use by researchers and practitioners.…”
Section: Measurement Of Police-communtiy Interactionsmentioning
confidence: 99%
“…Such a system could help realize the positive impacts of adopting BWCs, for which an extensive related literature has documented at most only inconsistent improvements for police-community interactions, police and community member perceptions, police investigations, and police organization (see Lum et al, 2019Lum et al, , 2020. Validated measurement tools to code the content of BWC footage are currently limited in their ability to capture police-community interactions and meaningfully evaluate officer behavior and decision making (Sytsma et al, 2021). The development of such tools remains in the early stages of research for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, it can be challenging to widely use by research assistants or police practitioners for example. That said, SSO has been used to code BWC footage of use-of-force encounters for officer adherence to procedural justice standards (Systma et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Body Worn Cameras (BWCs) provide an alternative approach for analyzing how police perform during encounters with the public, as well as investigating what factors might influence the outcomes of these encounters. Researchers are starting to take advantage of BWC footage to assess officer behavior such as incivility (Holladay & Makin, 2021) and adherence to procedural justice standards (Sytsma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%